2014
DOI: 10.7863/ultra.33.10.1755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound Sonication on Clonogenic Survival and Mitochondria of Ovarian Cancer Cells in the Presence of Methylene Blue

Abstract: Ultrasound sonication in the presence of methylene blue markedly damaged mitochondrial structure and function and decreased clonogenic survival of HO-8910 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…MB is FDA approved for use in globinemia, and it has received increasing attention for use in clinical applications, including diagnosis and histological staining 18,19. Furthermore, MB can work as sonosensitizer for sonodynamic therapy,20,21 as well as photoacoustic (PA) imaging contrast agent,22 which benefit to early diagnosis is another important aspect of theranostics. However, some drawbacks of MB have limited its further clinical applications for tumor treatment, such as inactivation in the biological environment through chemical changes to colorless MB and poor tumor localization 23.…”
Section: Introductionmentioning
confidence: 99%
“…MB is FDA approved for use in globinemia, and it has received increasing attention for use in clinical applications, including diagnosis and histological staining 18,19. Furthermore, MB can work as sonosensitizer for sonodynamic therapy,20,21 as well as photoacoustic (PA) imaging contrast agent,22 which benefit to early diagnosis is another important aspect of theranostics. However, some drawbacks of MB have limited its further clinical applications for tumor treatment, such as inactivation in the biological environment through chemical changes to colorless MB and poor tumor localization 23.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the influence of ultrasound, methylene blue alone and together to ovarian cancer cells, we observed more seriously damaged mitochondria, even with almost complete disappearance of cristae in the cells treated by ultrasound sonication in the presence of methylene blue than others (Xiang et al, 2014). So methylene blue may be a potential sonosensitizer.…”
Section: Other Sonosensitizersmentioning
confidence: 81%
“…Previously, Sura et al (2001) determined that continuous ultrasound waves (generated using a 25-kHz magnetostrictive transducer and TFI-1 chisel-shaped tip, with tip displacement set at 9.84, 12.23 or 18.20 mm, over a period of 30 s) caused rat osteoblasts to detach and lose viability whether the cells were in suspension or attached to the Petri dish in the period 0À20 h after exposure. It is also known that ultrasound causes mitochondrial dysfunction and autophagy in nasopharyngeal carcinoma cells (Li et al 2018) and mitochondrial enlargement in ovarian cancer cells (Xiang et al 2014). Recently, Wang et al (2019) used microarray data from NCBI GEO Dataset databases to perform mining analysis, which indicated that low-intensity ultrasound activated different cell death transcription factors (299 death regulators) in cancerous or non-cancerous cells (total of 13 different cell types) and changed the redox status of the cells, known to be linked to mitochondrial damage (Pelicano et al 2004).…”
Section: Discussionmentioning
confidence: 99%